2020
DOI: 10.1177/1076029619895120
|View full text |Cite
|
Sign up to set email alerts
|

Assay-Based Differentiation in the Neutralization Profile of Unfractionated Heparin, Enoxaparin, and Fondaparinux by Andexanet Alfa

Abstract: Andexanet alfa is a recombinant factor Xa decoy protein, designed to reverse bleeding associated with oral anti-Xa agents. Andexanet alfa is also reported to neutralize the effects of heparin-related drugs. This study focused on the neutralization profiles of unfractionated heparin (UFH), enoxaparin, and, a chemically synthetic pentasaccharide, fondaparinux by andexanet alfa. Whole blood clotting studies were carried out using thromboelastography (TEG) and activated clotting time (ACT). The anticoagulant profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…In the in-vitro study by Siddiqui et al, not only were whole blood coagulation tests assessed but also assays with pooled plasma and constant AT levels. 4 In the coagulation tests (activated partial thrombin time, thrombin time) the effect of UFH was nearly completely reversed by andexanet alfa. In contrast, in the chromogenic anti-Xa and anti-IIa assays, andexanet alfa only demonstrated a modest reversal of UFH action.…”
Section: A Novel and Dramatic Case Is Reported In The Current Issue Omentioning
confidence: 94%
See 2 more Smart Citations
“…In the in-vitro study by Siddiqui et al, not only were whole blood coagulation tests assessed but also assays with pooled plasma and constant AT levels. 4 In the coagulation tests (activated partial thrombin time, thrombin time) the effect of UFH was nearly completely reversed by andexanet alfa. In contrast, in the chromogenic anti-Xa and anti-IIa assays, andexanet alfa only demonstrated a modest reversal of UFH action.…”
Section: A Novel and Dramatic Case Is Reported In The Current Issue Omentioning
confidence: 94%
“…In contrast, in the chromogenic anti-Xa and anti-IIa assays, andexanet alfa only demonstrated a modest reversal of UFH action. 4 In most commercially available chromogenic assays, an excess of AT is added to the substrate to ensure adequate monitoring of heparin levels. Apparently, this was not the case in this investigation.…”
Section: A Novel and Dramatic Case Is Reported In The Current Issue Omentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,15 Andexanet is the only product available on the market with supporting data; however, there are only few published in vitro studies assessing the use of andexanet for reversal of UFH. 10,12-15…”
Section: Andexanet Alfa For Reversal Of Ufhmentioning
confidence: 99%
“…Siddiqui et al 12 reported that andexanet produced an almost complete neutralization of UFH anticoagulation effects and reversed the TEG profile to near normal. The study was done using freshly drawn blood samples from healthy individual donors and did not utilize protamine as comparator.…”
Section: Andexanet Alfa For Reversal Of Ufhmentioning
confidence: 99%